2009
DOI: 10.1590/s0102-76382009000500012
|View full text |Cite
|
Sign up to set email alerts
|

Tendências em experimentação animal

Abstract: Introduction: Animal models have been developed for scientific research over the last few decades in an attempt to comprehend etiological factors and mechanisms and to treat diseases.Objective: The aim of this article was to discuss aspects related to animal experimentation, the choice of animal models and the current trends in Brazil. Additionally, this study aims at evaluating the space occupied by experimental articles in medical journals.Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…Researches in vivo are classified into four categories, according to the model of experimentation: 1) induced -situations where the condition/disease investigated is being experimentally induced; 2) spontaneous -uses genetic variants of human diseases that occur naturally in animals; 3) negative -uses animals, in which a specific disease does not develop or that demonstrate a lack of reactivity to a specific stimulus; 4) orphan -a condition which occurs naturally in animals under conditions not described in humans and later adopted when the disease is identified in humans (2)(3) .…”
Section: Experimental Research With Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researches in vivo are classified into four categories, according to the model of experimentation: 1) induced -situations where the condition/disease investigated is being experimentally induced; 2) spontaneous -uses genetic variants of human diseases that occur naturally in animals; 3) negative -uses animals, in which a specific disease does not develop or that demonstrate a lack of reactivity to a specific stimulus; 4) orphan -a condition which occurs naturally in animals under conditions not described in humans and later adopted when the disease is identified in humans (2)(3) .…”
Section: Experimental Research With Animal Modelsmentioning
confidence: 99%
“…Presupposes conducting pilot studies to identify potential problems, the exact use of test animals and their controls, obtaining as much information as possible about the study before its initiation, previous statistical prediction of the study, minimization of environmental variables such as disease, stress and diet that may affect the results and, finally, selecting the appropriate species for that purpose (4,11,13) . The animals used in research should meet ideal conditions, ie, must be kept in controlled environment to maintain the health and genetic parameters, to ensure uniformity in relation to environmental, genetic and experimental variables (2)(3) . The sample size can be estimated by mathematical relationship between the value of the studied effect (the biologically significant difference), the standard deviation (usually obtained from a pilot), the level of significance (usually between 0.05 and 0.01) and power of the test (usually between 80 and 90%) (14) .…”
Section: The Principles Of Experimental Research With Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A busca do entendimento de mecanismos e tratamento das doenças tem levado ao desenvolvimento de vários modelos animais de lesões ou outras patologias. Para que essas sejam investigadas a condição ou doença é induzida de forma experimental [6]. O uso do modelo animal permite superar limitações de estudos com humanos, como alguns aspectos éticos de experimentação em seres humanos e obtenção de número suficiente de casos com características homogêneas [7].…”
Section: Introductionunclassified
“…The domestic pig is still widely used as an animal model for the study of human disease, and has been shown to be similar to man for biological, anatomic, physiological and nutritional characteristics 10 . However, it has relatively high market value for use in scientific experimentation because of its maintenance.…”
Section: Introductionmentioning
confidence: 99%